Virtual prototyping of a semi-active transfemoral prosthetic leg. (May 2015) - Lui, Zhen Wei; Awad, Mohammed I; Abouhossein, Alireza; Dehghani-Sanij, Abbas A; Messenger, Neil
This article presents a virtual prototyping study of a semi-active lower limb prosthesis to improve the functionality of an amputee during prosthesis–environment interaction for level ground walking. Articulated ankle–foot prosthesis and a single-axis semi-active prosthetic knee with active and passive operating modes were considered. Data for level ground walking were collected using a photogrammetric method in order to develop a base-line simulation model and with the hip kinematics input to verify the proposed design. The simulated results show that the semi-active lower limb prosthesis is able to move efficiently in passive mode, and the activation time of the knee actuator can be reduced by approximately 50%. Therefore, this semi-active system has the potential to reduce the energy consumption of the actuators required during level ground walking and requires less compensation from the amputee due to lower deviation of the vertical excursion of body centre of mass.